Pelaksanaan Tanggung Jawab Orang Tua Terhadap Anak Pasca Perceraian di Wilayah Hukum Pengadilan Negeri Jambi - Lolanda Sinaga; Umar Hasan; Permono Permono (Zaaken: Journal of Civil and Business Law, 2020)
The purpose of this study is to know and analyze the responsibilities of parents towards children after divorce in the jurisdiction of the Jambi District Court. 2. To find out and analyze the obstacles faced in implementing the responsibilities of parents towards children after the divorce in the Jurisdiction of the Jambi District Court. The method used is empirical juridical research type. The formulation of the problem under study regarding the responsibilities of parents towards post-divorce children in the jurisdiction of the Jambi District Court 1. How to implement the responsibilities of parents towards post-divorce children in the jurisdiction of the Jambi District Court; 2. Whatever is the obstacle in the implementation of parental responsibilities towards children after divorce in the jurisdiction of the Jambi District Court. The results of the study show that 1. the implementation of parental responsibilities towards children after divorce in the jurisdiction of the Jambi District Court is not fully implemented 2. the constraints in the implementation of parental responsibilities towards children after divorce in the jurisdiction of the Jambi District Court are the lack of awareness of people parents will have a good future for children, a factor in the inability of parents to finance the financial needs of children. Keywords: Responsibility of Parents, Children, Divorce.   Abstrak Tujuan dari penelitian ini adalah 1.untuk mengetahui dan menganalisis tanggung jawab orang tua terhadap anak pasca perceraian di wilayah hukum Pengadilan Negeri Jambi. 2. Untuk mengetahui dan menganalisis kendala yang dihadapi dalam pelaksanaan tanggung jawab orang tua terhadap anak pasca terjadinya perceraian di Wilayah Hukum Pengadilan Negeri Jambi. Metode yang digunakan adalah tipe penelitian yuridis empiris. Adapun perumusan masalah yang dikaji mengenai Bagaimana tanggung jawab orang tua terhadap anak pasca perceraian di wilayah hukum Pengadilan Negeri Jambi 1. Bagaimana pelaksanaan tanggung jawab orang tua terhadap anak pasca perceraian di wilayah hukum Pengadilan Negeri Jambi; 2. Apasaja yang menjadi kendala dalam pelaksanaan tanggung jawab orang tua terhadap anak pasca terjadinya perceraian di wilayah hukum Pengadilan Negeri Jambi. Hasil dari penelitian menunjukkan bahwa 1. pelaksanaan tanggung jawab orang tua terhadap anak pasca perceraian di wilayah hukum Pengadilan Negeri Jambi tidak dilaksanakan secara penuh 2. kendala dalam pelaksanaan tanggung jawab orang tua terhadap anak pasca terjadinya perceraian di wilayah hukum Pengadilan Negeri Jambi yaitu kurangnya kesadaran orang tua akan masa depan yang baik bagi anak, faktor ketidakmampuan orang tua untuk membiayai kebutuhan keuangan bagi anak. Kata Kunci : Tanggung Jawab Orang Tua, Anak, Perceraian.